Sn(1-x)LaxO2 thin films deposited on AISI 304 stainless steel substrates - Goncalves, Paulo R. G.; Rangel, Jose H. G.; Oliveira, Marcelo M.; Maciel, Adeilton P.; Longo, Elson [UNESP] (Elsevier B.V., 2014)
To minimize the corrosive processes that affect metal structures, this work involved the synthesis of Sn(1-x)LaxO2 ceramic thin film deposited on AISI 304 steel. The polymeric precursor method was used here to obtain resin precursors of Sn(1-x)LaxO2 films with x=1, 3 and 5 mol%. The films were deposited using dip-coating and spin-coating techniques to ensure better packing, and were then heat-treated in a muffle furnace at temperatures of 400, 450 and 500 degrees C for two hours. The SnO2 samples and the organic precursors were morphologically and structurally characterized by X-ray diffraction (XRD), thermogravimetric and differential thermal analysis (TG-DTA), Raman spectroscopy, atomic force microscopy (AFM) and scanning electron microscopy (SEM). These characterizations revealed crack-free, single-phase, dense thin films with good adhesion to the metal substrate in the entire temperature range employed in this study. (C) 2014 Elsevier Ltd and Techna Group S.r.l. All rights reserved.
Keywords: Films; Sn(1-x)LaxO2; Steel